Advancements in Protein Kinase Inhibitors: From Discovery to Clinical Applications - Salem Baldi; Nanbiao Long; Shu Ma; Li Liu; Abdullah Al-Danakh; Qin Yang; Xinpei Deng; Jindong Xie; Hailin Tang (Research)
Protein kinases are key mediators of cellular signaling and control cell functions through the phosphorylation of target proteins. They have become major targets for therapeutic agents aimed at treating human diseases, particularly cancer. Protein kinase inhibitors (PKIs) have emerged at the forefront of drug development, and their investigations continue to be intense, with several candidates undergoing clinical trials and persistent endeavors to identify new chemical scaffolds. The main focus is still on developing isoform-selective compounds, which are inhibitors designed to target certain protein kinases, specifically isoforms, for more precise treatment. The identification and advancement of versatile inhibitor scaffolds that more effectively target individual kinases is essential for minimizing off-target effects and resistance. This review highlights important progress in PKI therapy, emphasizing the expansion of treatments for cancer, inflammatory diseases, and neurodegenerative diseases. Future efforts should focus on improving the specificity of inhibitors via mechanistic insights, developing combination therapies, establishing novel strategies, such as CRISPR-Cas9 integration with artificial intelligence-driven drug design, and overcoming resistance to enhance clinical treatment outcomes. Clinical case stories show the challenges and possible opportunities in this quickly evolving area.